First Time Detection Of Brome Mosaic Virus Associated With Other Wheat Viruses In Kansas Wheat Using Nanopore Sequencing - Ranabhat, Nar B.; Fellers, John; Bruce, Myron; Rupp, Jessica (My University, 2021)
Kansas wheat production has been threatened by Wheat streak mosaic complex of three viruses including Wheat streak mosaic virus (WSMV). Triticum mosaic virus (TriMV), and High Plains wheat mosaic emaravirus (HPWMOV). In 2017. Kansas wheat producers lost 19.2 million bushels of wheat worth $76.8 million due to wheat streak mosaic. Infection of a single plant with multiple viruses is common in wheat fields. Other common wheat viruses have been recorded from Kansas but not the Brome mosaic virus (BMV) Diagnosis of virus like symptoms in plants has been mostly dominated by targeted-specific methods with known antibodies, primers, and probes. These targeted methods identify only already known viruses and virus combinations Next generation sequencing techniques such a Nanopore sequencing technology has great potential for identifying novel and multiple potential plant pathogens in a single analysis. Reliable diagnostic methods are needed to identify the risks in plant health to develop appropriate plant protection strategies.